Regulation of calcium channels in brain: implications for the clinical neurosciences. - Taft, W. C. (Yale Journal of Biology and Medicine, 1987)
Calcium is a major second messenger in neurons and modulates many neuronal functions, including protein phosphorylation, phospholipid metabolism, cytoskeletal activity, and neurotransmitter release. These important events, which regulate neuronal activity, are directly dependent on the influx of extracellular calcium through voltage-sensitive calcium channels (VSCCs) in the neuronal membrane. Modulation of VSCC function represents an important strategy for regulating neuronal excitability. Although substantial evidence supports the ability of dihydropyridines to block VSCCs and contractility in cardiovascular tissue, their ability to block the majority of neuronal VSCCs remains controversial. Benzodiazepines, and other anticonvulsants, block depolarization-dependent 45Ca uptake through VSCCs in brain synaptosome preparations. In addition, benzodiazepines reduce voltage-gated calcium conductance as determined by voltage clamp studies of identified invertebrate neurons. Inhibition of VSCC activity may be an important mechanism by which these compounds produce their anticonvulsant and sedative effects. Intrasomal injection of calcium-calmodulin-dependent protein kinase modulates calcium conductance in invertebrate neurons, suggesting that protein phosphorylation may be an endogenous regulatory mechanism of VSCC activity. Developing novel pharmacological approaches to regulating VSCCs and understanding the endogenous regulatory mechanisms may lead to new therapeutic approaches to the treatment of neurological diseases.